Imaging of Soft-Tissue Pseudotumors: A Pictorial Review - Chaudhary, Priya; Satija, Bhawna; Solanki, RS; Lal, Romesh; Agarwal, Kiran (Indographics, 2024)
Soft-tissue pseudotumors are a myriad group of clinically palpable masses that mimic soft-tissue tumors. These mimickers may be misinterpreted as malignant sarcomas despite appropriate clinical and radiological evaluation, resulting in unwarranted interventions and a diagnosis of a pseudotumors is achieved only after histopathological evaluation. A systematic approach is needed to achieve a definitive diagnosis or to limit the differential diagnosis by using imaging in conjunction with clinical history, physical examination, and anatomical location. The objective of this article is to provide an overview of the imaging features of some of the most common soft-tissue pseudotumors. Recognition of these pseudotumors is of paramount importance as no further investigation or intervention may be required in majority of the cases.
Keywords: pseudotumors; soft-tissue mass; tumor mimic